Reputation Communication of Online Companies - Boer, Rino F (Ikatan Sarjana Komunikasi Indonesia, 2018)
Nowdays, technology & information development has opened trading through the internet. Digital trading better known as e-commerce is growing rapidly with support of digital communication facilities. Bukalapak.com is the research object because Bukalapak.com is one of the famous online selling sites in Indonesia which experience a decline in performance since its started on 2010 from its several digital indicators. One important aspect for online company is digital service. How does the digital service quality/e-ServQual affect the company's reputation? The purpose of this study is to analyze the e-ServQual influence on consumer trust, analyze the influence of consumer trust on corporate reputation, and analyzieng the effect of e-ServQual on companies mediated by consumer trust in Bukalapak.com users. The population of this study is 111 members of the community of Bukalapak Jakarta. Data was collected through surveys and questionnaire distribution and data analysis used is path analysis. The results of the study showed that e-ServQual has unsignificant negative on corporate reputation (direct effect), e-ServQual has a significant positive effect on consumer trust, consumer trust has a positive effect on corporate reputation, and e-ServQual has significant positive effect on corporate reputation mediated by consumer trust (indirect effect).